Fluoridation of the public water supply and prevalence of dental fluorosis in a peripheral district of the municipality of Bauru, SP Fluoretação da água de abastecimento público e prevalência de fluorose dentária em bairro da periferia de Bauru, SP - Irene Ramires; Kelly Polido Kaneshiro Olympio; Andréa Gutierrez Maria; Juliano Pelim Pessan; Vanessa Eid Silva Cardoso; Carolina Simonetti Lodi; Marília Afonso Rabelo Buzalaf (University of São Paulo, 2006)
OBJECTIVES: The objectives of this study were to assess the fluoride concentration in the public water supply and the prevalence of dental fluorosis in schoolchildren between 7 and 15 years old, living in a peripheral district of the municipality of Bauru. MATERIAL AND METHODS: For this, fifty two water samples were collected on three different days of one week. These samples were analyzed for fluoride by means of the ion-sensitive electrode method (Orion 9609) coupled to a potentiometer (Procyon, model 720). In this method, 1.0 mL of TISAB II (Orion) was added to 1.0 mL of the sample. For the epidemiological survey of fluorosis, 52 schoolchildren of both genders, aged between 7 and 15 were assessed, with prior authorization from their caretakers. Only one person examined the children, after supervised toothbrushing and drying with cotton wool rolls. The TF index was used. RESULTS: The fluoride concentrations in the water samples ranged from 0.62 to 1.20 mg/L, with a mean of 0.9 mg/L. The prevalence of dental fluorosis was 33%, with severity ranging from TF1 to TF4 (Kappa of 0.73 and concordance of 83.33%). CONCLUSIONS: The results from the analysis of water samples indicated a fluoride concentration greater than recommended for Bauru. The fluorosis levels found were higher than expected for a peripheral district, in which water is one of the few sources of fluoride. OBJETIVOS: Avaliar a concentração de flúor na água de abastecimento público e a prevalência de fluorose dentária de escolares entre 7 e 15 anos de idade, residentes em um bairro da periferia de Bauru. MATÉRIAL E MÉTODOS: Foram coletadas 52 amostras de água durante três dias de uma semana e analisadas utilizando-se o eletrodo íon sensível (Orion 9609), acoplado a um potenciômetro (Procyon, modelo 720), com 1,0 mL da amostra à qual foi adicionado 1,0 mL de TISAB II (Orion). Para o levantamento epidemiológico de fluorose foram examinados 52 escolares entre 7 e 15 anos de idade, de ambos os gêneros, mediante a obtenção de autorização prévia dos responsáveis. Somente um examinador realizou os exames após escovação supervisionada e secagem dos dentes com rolos de algodão. O índice utilizado foi o TF, estabelecido a partir do grau máximo verificado em cada indivíduo. RESULTADOS: A concentração de flúor na água variou entre 0,62 e 1,15 mg/L, mantendo uma média de 0,9 mg/L. A prevalência de fluorose dentária verificada foi de 33%, com severidade variando entre TF1 e TF4 (Kappa=0,73 e concordância de 83,33%). CONCLUSÕES: Os resultados da análise das amostras de água indicam uma concentração média de flúor acima do recomendado para Bauru. O índice de fluorose dentária verificado foi maior que o esperado para um bairro da periferia, onde a água é uma das poucas fontes de ingestão de flúor.